The Effectiveness Of Developing An Adaptive Physics E-Module In Moodle-Based Blended Learning On Students' Representation Ability On Thermodynamics Material - Swastika Ramadhanty Eka Putri; Khumaedi Khumaedi; Budi Naini Mindyarto (Universitas Muhammadiyah Enrekang, 2023)
The research aims to develop adaptive electronic modules using Moodle-based blended learning as a solution to improve representation skills in the school environment. This research combines online and face-to-face learning methods (blended learning) with the use of Moodle as a digital learning platform. Three forms of representation in the concept of physics, are (1) verbal representation; (2) visual representation; and (3) mathematical representation. The formulation of the problem in this research is the characteristics, validity, and effectiveness of the E-module. This module aims to provide learning content that is tailored to the needs and abilities of each individual student. Adaptive features allow students to access materials, assignments, and learning resources appropriate to their skills level. Learning is done through a combination of classroom teaching and e-modules through Moodle. E-module development model uses the research and development method. The research design used is a true experimental design in the form of a